Opium regimes : China, Britain, and Japan, 1839-1952 - Brook, Timothy, 1951-; Wakabayashi, Bob Tadashi, 1950- (University of California Press, 2000)
Opium Regimes draws on a range of research to show that the opium trade was not purely a British operation, but involved Chinese merchants and state agents, and Japanese imperial agents as well.
Keywords: Opium trade -- China -- History.; Drug traffic -- China -- History.; Drug control -- China -- History.; China -- Relations -- Great Britain.; Great Britain -- Relations -- China.; China -- Relations -- Japan.; Japan -- Relations -- China.; Opium -- Commerce -- Chine -- Histoire.; Drogues -- Trafic -- Chine -- Histoire.; Lutte antidrogue -- Chine -- Histoire.; SOCIAL SCIENCE -- General.; BUSINESS & ECONOMICS -- Infrastructure.; Drug control; Drug traffic; Opium trade; International relations; China; Great Britain; Japan; History